AUTOTRANSPLANTASI GIGI-GIGI IMPAKSI INSISIVUS MAKSILA KANAN DISERTAI KISTA DENTIGEROUS DENGAN PENAMBAHAN GRAFT KOLAGEN KARBONAT APATIT - Indah Wulansari; Maria Goreti Widiastuti; Prihartiningsih Prihartiningsih (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Autotransplantation is a surgical movement to reposition teeththat have been erupted, partially erupted or not yet erupted from one place to another in the same individual, either on post-extraction sockets or artifcial sockets made by surgery. Dental folicle from impacted teeth may develope dentigerous cysts that will result in destruction of the jaw bone. There are many factors that inﬂuence the success of autotransplantation, one of which is adequate bone support.The purpose of this poster is to present the successful autotransplantation treatment of impacted right maxillary incisor teeth associated with dentigerous cyst and bone support replacement after cyst enucleation using a carbonate apatite collagen graft, GAMACHA®, at RSUP Dr. Sardjito.Case management: A 9-year-old girl, referred to the Oral and MaxillofacialSurgery Department of RSUP Dr. Sardjito with the complaint of right deciduous maxillary incisor persistence. Radiological examination showing persistent of 51 and 52 radices and impaction of teeth 11 and 12 in a horizontal position above radix 53. Also visible radiolucent image with a frm limit around the crown of 11 that supports the image of cyst. This patient performed cyst enucleation under general anesthesia, removal of impacted 11 and 21, followed by an artifcial socket drilling at the alveolar bone that could support all aspects of the root wall although only on the apical part of the tooth root for teeth 11 and 12 placement. Autotransplantation of teeth11 and 12 followed by the application of GAMACHA® and wire fxation, strengthen with acrylic splint.Conclusion: Two years follow up after surgery, patient have no complaintseither from aesthetic or functional and the result of clinical and radiologicalexamination did not found existence of any pathological abnormalities around teeth 11 and 12.